A Comparation study: Cooperative Learning in Science Learning - Zurweni, Zurweni; Kurniawan, Dwi Agus; Triani, Elza (Jurnal Pendidikan dan Pengajaran, 2022)
The formulation of the problem in this study is how to compare student responses to the jigsaw and STAD learning models in science subjects at SMPN 34 Batanghari, SMPN 35 Batanghari, MTsN 5 Batanghari and MTsN 7 Batanghari and How are students' responses to the jigsaw and STAD learning model at SMPN 34 Batanghari , SMPN 35 Batanghari, MTsN 5 Batanghari and MTsN 7 Batanghari. This type of research is a quasi-experimental quantitative research by comparing 8 classes that use the jigsaw and STAD models in science learning. This research was carried out in 4 schools, namely 2 SMP and 2 MTs with 35 students in each class, the total number of students is 280 students . In data analysis using SPSS 26. Based on the results of the T test, namely the value of sig. (2-tailed < 0.05), it can be said that there is a difference between student responses with the Jigsaw and STAD learning models in science subjects in SMP/MTs .